2020
DOI: 10.1136/jmedgenet-2019-106658
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic exome sequencing in non-acquired focal epilepsies highlights a major role of GATOR1 complex genes

Abstract: BackgroundThe genetic architecture of non-acquired focal epilepsies (NAFEs) becomes increasingly unravelled using genome-wide sequencing datasets. However, it remains to be determined how this emerging knowledge can be translated into a diagnostic setting. To bridge this gap, we assessed the diagnostic outcomes of exome sequencing (ES) in NAFE.Methods112 deeply phenotyped patients with NAFE were included in the study. Diagnostic ES was performed, followed by a screen to detect variants of uncertain significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…4,5 Whole-exome sequencing (WES) case-control studies have led to multiple insights into the epilepsies, such as the contribution of de novo variants in developmental and epileptic encephalopathy (DEE [MIM: 308350]), the role of the GABA pathway in genetic generalized epilepsy (GGE [MIM: 600669]), and the link between non-acquired focal epilepsy (NAFE [MIM: 604364, 245570]) and GATOR1 complex genes. [6][7][8][9][10] DEEs are a severe form of early onset, intractable epilepsy associated with developmental delay. 8,[11][12][13][14] In contrast, GGE and NAFE, characterized by generalized seizures and focal seizures, respectively, are more common and generally less severe.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Whole-exome sequencing (WES) case-control studies have led to multiple insights into the epilepsies, such as the contribution of de novo variants in developmental and epileptic encephalopathy (DEE [MIM: 308350]), the role of the GABA pathway in genetic generalized epilepsy (GGE [MIM: 600669]), and the link between non-acquired focal epilepsy (NAFE [MIM: 604364, 245570]) and GATOR1 complex genes. [6][7][8][9][10] DEEs are a severe form of early onset, intractable epilepsy associated with developmental delay. 8,[11][12][13][14] In contrast, GGE and NAFE, characterized by generalized seizures and focal seizures, respectively, are more common and generally less severe.…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic or likely pathogenic variants in the DEPDC5, NPRL2 and NPRL3 genes were identified in 8–11% of individuals within focal epilepsy cohorts, mostly comprised of familial non-lesional cases. 3 , 4 , 63 The frequency of GATOR1-related epilepsies in these studies is likely over-estimates of their true prevalence due to the enrichment of familial cases in the cohorts. Large international collaborative studies have demonstrated the contribution of ultra-rare variation in known epilepsy genes to common epilepsies, like non-acquired focal epilepsy.…”
Section: Personalized Medicine In Mtoropathy-related Epilepsiesmentioning
confidence: 96%
“… 11 Seizures usually begin in childhood or adolescence but the age of first seizure has ranged from the first days of life to older than 50 years. 3 , 11 , 63 , 111 Importantly, over half of individuals with GATOR1-related epilepsies have DRE ( Table 3 ). 11 …”
Section: Personalized Medicine In Mtoropathy-related Epilepsiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 However, molecular diagnostic rates with genomic sequencing vary across testing indications, 3 and may also differ substantially between patients with the same disease entity depending on individual phenotypic factors. [4][5][6][7] There is a clinically and economically grounded need to identify patients who are more likely to carry pathogenic DNA variation detectable by genomic sequencing, and therefore would be more likely to benefit from such testing. 8,9 Recently, we took advantage of a very large collection of whole-exome sequencing (WES) data from patients with dystonia to isolate clinical variables significantly associated with diagnostic outcome; these included (i) an onset of dystonia before the age of 21 years, (ii) a manifestation of segmental or generalized dystonia, and (iii) a combination of dystonia with non-dystonic neurological features (other movement disorders and/or non-movement disorder-related symptoms).…”
Section: Introductionmentioning
confidence: 99%